Authority, Legitimacy, and Support for Armed Groups: A Case Study of the Ejército Zapatista de Liberación Nacional. Issue 3 (3rd July 2019) - Ross, Nicholas
ABSTRACT: This paper applies a model of the relationship between armed group authority/legitimacy and popular support for armed groups, to explain how the EZLN gained support among a diverse array of constituencies in the period from 1983-2005. Moreover, it shows that the need to maximise support explains the EZLN's strategy in the different phases of its existence. The EZLN is an interesting case, due to the organization's high degree of reliance on international and national civil society support, which illustrates the importance of ideology and political messaging in understanding support for armed groups.